Elimination of antibiotic resistance genes from excess activated sludge added for effective treatment of fruit and vegetable waste in a novel vermireactor. (April 2021) - Li, Wenjiao; Li, Jiefeng; Ahmad Bhat, Sartaj; Wei, Yongfen; Deng, Zhiyi; Li, Fusheng
Graphical abstract: Highlights: Novel vermireactors consist of substrate and bed compartments were established. ARGs & intl 1 from EAS added for effective treatment of FVW were eliminated. Relative abundances of ARGs & intl 1 in fresh cast samples were reduced markedly. Earthworms' gut could selectively digest the host bacteria harboring ARGs & intl 1 . Abstract: Elimination of antibiotic resistance genes (ARGs) from excess activated sludge (EAS) mixed for effective treatment of different fruit and vegetable waste (FVW) by using a novel vermireactor consisted of substrate and bed compartments was investigated. ARGs ( tet G, tet M and sul 1 ) and mobile genetic element gene ( intl 1 ) were targeted and, through quantitative analysis of their abundances in both the compartments and the fresh cast of earthworms, significant reductions in substrate compartments were confirmed for the treatments for FVW added with EAS and EAS alone even if the reduction extents differed among the types of FVW. Apparent reductions were not found in the bed compartment where the final products accumulated. For the fresh cast, the relative abundances of ARGs and intl 1 against to the total bacterial 16S rDNA decreased markedly. The present study provided an insight for proper controlling of ARGs during vermicomposting of FVW and EAS.